PERSPECTIVES AND OPPORTUNITIES OF GROATS PRODUCTION IN UKRAINE - S. Sots; I. Kustov; O. Mashchenko (Zernovì Produkti ì Kombìkorma, 2023)
Since the beginning of the 21st century, there has been an increase in the share of small enterprises in the grain industry, the number of which is increasing even today. At most of such enterprises, it is impossible to apply the existing longterm full grain processing technologies, there is a reduction in the number of basic technological operations, often not sufficiently substantiated, which affects the quality of the end products, which do not always meet all the basic norms of the regulations applicable to end products. Considering the modern technological solutions offered by leading manufacturers for the production of flaked products and quick-cooking products, it is possible to note the equipment of the Buhler company, which allows to monitor production control and, accordingly, achieve greater production efficiency. To date, the Buhler company offers the batch steamer MBDA for the steaming stage, which is recommended to be combined with the BCFB flaking machine. This technological equipment in combination gives high quality and reliability of the equipment itself, allows to implement energy-saving technologies at enterprises and obtain controlled production of quality products. Today, in addition to traditional grain, such crops as lentils, chickpeas, beans, wheat-spelt, spelt, naked varieties of oats and barley are processed in part or in small batches at the enterprises of the industry. Lentil is a promising leguminous crop for the grain industry. In the world, it is widely grown as a food and fodder crop. Among leguminous crops, lentils occupy an intermediate place in terms of protein content, with a protein content of 25-36%, while the share of carbohydrates is 45-55%, fat - 3-4%. The first variety of «Linza» edible lentils was registered in 2005. After that, the following varieties were registered only in 2017-2018: «Antonina» (2017), «Darinka» (2017), «YeSMaksymum» (2017), «Blondie» (2018), «Harry» (2018), «SNIM 18» (2018), Chrysolite (2018), which indicates an understanding of the potential of this culture both for the domestic market and for increasing the export potential of our country. The last to enter the register were «Serpanok» (2020) and «RED» (2021) varieties, which indicates the continued work of breeders to expand the varietal base of this crop in Ukraine.